Examination of microsatellite markers of Dorper sheep breed - Csizmár, Nikolett; Jávor, András; Kusza, Szilvia (Acta Agraria Debreceniensis, 2016)
Number of not woolly and molty sheep exceeds 60 million throughout the world. Their numbers and their importance is growing, still they have appeared in the past two decades all over in North-America, Australia, New-Zealand and also in Europe. The South African Dorper has been a pioneer among them in Hungary. It was introduced in 2006 in the country. The Dorper sheep is the second largest breed in South Africa, which was developed from the crossing of Dorset Horn and the Blackhead Persian. The aim of the EU Member States in terms of this specific breed is increasing the small populations, improving the productive qualities, in addition to this avoiding inbreeding. However, finding appropriate breeding stock is difficult due to the small size of available populations and also to the suspected common of origin. With the help of various molecular genetic methods we could get a total view of the genetic background of these flocks. Nowadays the most commonly known and used genetic markers are microsatellites, because their applications give fast, accurate and easily reproducible results. There is no specific descriptive information on the genetic background of Dorper populations in the various EU countries , also regarding diversity between populations. Therefore in our work we want to optimize the conditions of applicability of 31 selected microsatellite reactions as a first step of mapping the entire genetic background of the different EU Dorper populations.